Two-sided reputation in certification markets - Matthieu Bouvard; Raphael Levy (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
We consider a market where privately informed sellers resort to certification to overcome adverse selection. There is uncertainty about the certifier's ability to generate accurate information. The profit of a monopolistic certifier is an inverted U-shaped function of his reputation for accuracy: being perceived as more precise allows to attract more good sellers but a high expected precision also deters bad sellers. Since the certifier tries to reach a balanced reputation to attract both types, reputation has a disciplining effect when the certifier is perceived as insufficiently accurate, but gives incentives to decrease precision when he is perceived as 'too accurate. The impact of competition depends on whether sellers 'multihome or 'singlehome. Under singlehoming, certifiers compete to attract good sellers, which makes higher reputation more valuable. Multihoming makes higher reputations less desirable because the competitor exerts a negative externality by providing extra information. Therefore, singlehoming attenuates bad reputation effects, while multihoming exacerbates inefficiencies.
urn:nbn:de:bvb:19-epub-17408-6
Keywords: 330